Radiographic Changes to Silver Diamine Fluoride Treated Carious Lesions after a Rinsing Step - Zaher Jabbour; Maryam Esmaeili; Marc Hayashi; Reuben Kim (MDPI AG, 2022)
Silver diamine fluoride (SDF) is radiopaque. This in vitro study compares the changes in the radiopacity of carious lesions after SDF application, potassium iodide (PI) application, and water rinse. Ten recently extracted human teeth were sectioned and divided into two groups (n = 10 in each group): Group 1 = SDF, Group 2 = SDF + PI. Teeth in Group 1 received SDF for 1 min and rinsed with 15 mL water. Group 2 received the same protocol with the addition of PI application for 1 min after SDF application. All samples were scanned with micro-computed tomography before SDF application, after SDF application, after PI application (group 2) and after water rinse. The radiopacity of the carious lesions increased significantly after SDF application in Group 1 and 2 (p < 0.017, p < 0.008, respectively). A significant increase in radiopacity after PI application was also observed in Group 2 (p < 0.008). Water rinsing significantly decreased the radiopacity in Group 1 and 2 (p < 0.017, p < 0.008, respectively), but the radiopacity remained significantly higher than the preoperative values (Group 1 p < 0.017, Group 2 p < 0.008). The radiopacity of carious lesions increases after SDF and SDF + PI applications. Water rinsing could reduce the radiopacity of SDF and SDF + PI treated carious lesions, and might reduce the content of SDF in carious lesions.